Activated interiors of clay nanotubes for agglomeration-tolerant automotive exhaust remediation1. Issue 12 (28th March 2015) - Sanchez-Ballester, Noelia M.; Ramesh, Gubbala V.; Tanabe, Toyokazu; Koudelkova, Eva; Liu, Jia; Shrestha, Lok Kumar; Lvov, Yuri; Hill, Jonathan P.; Ariga, Katsuhiko; Abe, Hideki
<x xml:space="preserve">Abstract</x> Naturally occurring clay nanotubes, halloysite, act as a high-performance exhaust catalyst when copper–nickel alloy nanoparticles are dispersed onto the interior surface.